FUNGSI PRODUKSI PUSAT KESEHATAN MASYARAKAT* - M. Yusril (Populasi, 1996)
This study on the productivity of the Community Health Centers was carried out in the province of Bengkulu. 31 Health Centers constituted the sample used in this study, which were then divided into three categories, that is, category 1, comprising of 1 Community Health Center, category 2, comprising of 17 Health Centers, and category 3, comprising of 13 Health Centers. This study was aimed at determining the factors which influence the productivity of Community Health Centers.The results of the study indicate that the role of leadership, the implementing work force, the place of service, the duration of the service, and the budget,allhavea positive influence on the productivity of the Community Health Centers. On the other hand however, the service charges, and the health service substitution has a negative influence on the productivity of the Community Health Centers. This paper shows that the role of government is still very dominant in improving on the productivity and the quality of the Community Health Centers, particularly in funding and deploying professional workforce (leaders, paramedics and non-paramedics).